Low-Molecular-Weight Chitosan Attenuates Lipopolysaccharide-Induced Inflammation in IPEC-J2 Cells by Inhibiting the Nuclear Factor-κB Signalling Pathway - Jiao Zhang; Jin Wan; Daiwen Chen; Bing Yu; Jun He (Molecules, 2021)
Low-molecular-weight chitosan (LMWC), a product of chitosan deacetylation, possesses anti-inflammatory effects. In the present study, a porcine small intestinal epithelial cell line, IPEC-J2, was used to assess the protective effects of LMWC on lipopolysaccharide (LPS)-induced intestinal epithelial cell injury. IPEC-J2 cells were pretreated with or without LMWC (400 μg/mL) in the presence or absence of LPS (5 μg/mL) for 6 h. LMWC pretreatment increased (p < 0.05) the occludin abundance and decreased (p < 0.05) the tumour necrosis factor-α (TNF-α) production, apoptosis rate and cleaved cysteinyl aspartate-specific protease-3 (caspase-3) and -8 contents in LPS-treated IPEC-J2 cells. Moreover, LMWC pretreatment downregulated (p < 0.05) the expression levels of TNF receptor 1 (TNFR1) and TNFR-associated death domain and decreased (p < 0.05) the nuclear and cytoplasmic abundance of nuclear factor-κB (NF-κB) p65 in LPS-stimulated IPEC-J2 cells. These results suggest that LMWC exerts a mitigation effect on LPS-induced intestinal epithelial cell damage by suppressing TNFR1-mediated apoptosis and decreasing the production of proinflammatory cytokines via the inhibition of NF-κB signalling pathway.